Targeting Proliferating Cell Nuclear Antigen (PCNA) as an Effective Strategy to Inhibit Tumor Cell Proliferation - Cardano, Miriana; Tribioli, Carla; Prosperi, Ennio (Current Cancer Drug Targets, 2020)
Targeting highly proliferating cells is an important issue for many types of aggressive tumors. Proliferating Cell Nuclear Antigen (PCNA) is an essential protein that participates in a variety of processes of DNA metabolism, including DNA replication and repair, chromatin organization and transcription and sister chromatid cohesion. In addition, PCNA is involved in cell survival, and possibly in pathways of energy metabolism, such as glycolysis. Thus, the possibility of targeting this protein for chemotherapy against highly proliferating malignancies is under active investigation. Currently, approaches to treat cells with agents targeting PCNA rely on the use of small molecules or on peptides that either bind to PCNA, or act as a competitor of interacting partners. Here, we describe the status of the art in the development of agents targeting PCNA and discuss their application in different types of tumor cell lines and in animal model systems.
Keywords: small molecules